ANALISA PENGARUH SPESIFIK PROYEK, LINGKUNGAN EKSTERNAL, DAN MANUSIA TERHADAP KINERJA PROYEK PT. KERETA API PROPERTI MANAJEMEN - Fissalam, Amirudin Syah; Hariadi, Agustinus (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2020)
The challenge in every construction project is to complete the project timely, profitably, and conforming predetermined quality. This study aims to examine and analyze effect of Project Specific, External Environment, and Human Factors on Project Performance of PT Kereta Api Properti Management (KAPM). It is a quantitative-type research. The research population is all employees who support the construction process at PT. KAPM which has been implemented in 2016 - 2018 totaling 110 people, using the Slovin method obtained a population sample of 87 people. The method of analysis used in this study is multiple linear regression. The study concludes that: Project Specific has a positive and significant effect on project performance of 29,4%, External Environment have a positive and significant effect on project performance of 12,4%, Human Factors have a positive and significant effect on project performance of 14,5%, Project Specific, External Environment, and Human Factors together have a significant effect on improving project performance of 73,4%, and Project Specific is variable that has the greatest influence on project performance of PT Kereta Api Properti Manajemen.